Endobronchial chondroma with ossification mimicking chronic obstructive pulmonary disease: a case report - Huang, Xiaoling; Xiong, Miaomiao; Jia, Zhiyong; Ran, Qijuan; Tang, Ping; Zhao, Shicai; Xiao, Min (Frontiers in Medicine, 2025)
BackgroundEndobronchial chondroma is a rare benign mesenchymal tumour, and its etiology remains not entirely understood. Due to the tumour’s slow growth rate, the early stages of the disease often present with atypical or nonspecific clinical symptoms. Consequently, most cases are discovered incidentally during examinations. However, when the tumour enlarges to partially or completely obstruct the bronchus or exerts pressure on adjacent structures, patients may present with a range of respiratory symptoms including fever, cough, sputum production, chest pain, stridor, dyspnea, and hemoptysis. These clinical manifestations lack specificity and can easily lead to misdiagnosis as chronic obstructive pulmonary disease (COPD), asthma, pneumonia, lung cancer and other common conditions. In some cases, they may even result in missed diagnoses. Therefore, in conjunction with relevant literature, we have summarized the diagnostic and therapeutic experiences of a case involving chronic obstructive pulmonary disease complicated by endobronchial chondroma with ossification at our hospital. We hope this will provide valuable insights for clinical practice.Case presentationA 67-year-old male farmer with a smoking history exceeding 30 years was admitted to the hospital due to persistent cough, expectoration, asthma for the past decade, and hemoptysis lasting more than 10 days. Upon admission, the patient received treatment with ceftazidime and bromhexine hydrochloride; however, no significant improvement was observed. Fiberoptic bronchoscopy revealed a neoplasm resembling paving stones in both the trachea and main bronchus, which was subsequently confirmed as endobronchial chondroma through pathological biopsy. Unfortunately, after receiving this diagnosis, the patient was discharged from the hospital without undergoing follow-up treatment. Although he was advised to return for review in 2–3 months and consider endoscopic intervention if necessary, he did not adhere to this schedule.ConclusionDespite being rare and lacking specific clinical manifestations or imaging characteristics, it is crucial to remain vigilant regarding potential uncommon diseases such as endobronchial chondroma in patients presenting with long-term cough, expectoration, asthma symptoms alongside a smoking history—even when common conditions like chronic obstructive pulmonary disease are initially suspected. When conventional treatments prove ineffective, timely examination via fiberoptic bronchoscopy should be conducted to prevent missed diagnoses of rare lesions like endobronchial chondroma due to symptom overlap with more prevalent diseases.